(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2020)
This paper looks at human development from an existential perspective. What is revealed is that human development is a lifelong process of the acquisition of the skills of living. Moreover that these are present in seven invariant themes that manifest in different ways throughout life. They are: age and ageing; narrative and autobiography; beginnings and endings; embodiment; randomness and chance; adversity; and love. These are considered in the light of psychotherapeutic practice.